Development of STEAM-Based Human Respiratory System Teaching Materials to Improve Students' Critical Thinking Skills - Wafi, Mumtaz Al; Lisdiana, Lisdiana; Sumarti, Sri Susilogati (Journal of Innovative Science Education, 2022)
This study aims to examine the validity of teaching materials and the effectiveness of STEAM-based human respiratory system teaching materials in improving students' critical thinking skills. The type of research used is research and development (R&D) which uses the ADDIE development model with a trial design of teaching materials using One Group Pretest-Posttest Design. The research subjects consisted of two material expert validators, one media expert validator, 7 subject teachers, and 143 class VIII junior high school students in Comal Pemalang Regency. The research instruments were in the form of needs analysis sheets, teaching materials validation sheets, and assessment instruments. The results of the validity of teaching materials by material and media experts obtained a very valid category. The results of the N-Gain analysis on the critical thinking indicator obtained a value of 0.68 in the medium category. STEAM-based human respiratory system teaching materials are feasible to use in learning and effective in improving students' critical thinking skills.